Pemilihan Kepala Desa, Teologi Politik, dan Peran Gereja: Analisis Kritis di Desa dan Jemaat Abat, Maluku - Salomi A Melatawun (Program Pascasarjana UKIM, 2022)
This research aims to describe the dynamics and impact of village head elections on the implementation of church services in Abat. The research was conducted using political theology theory as a means to present God's kingdom through the church. The church in its ministry must actively make changes as a form of presenting the kingdom of God in the middle of the world. This study uses a qualitative descriptive approach involving data collection procedures, data analysis, data processing, and data interpretation. The author finds that there are factors such as intervention, provocation, interests, village funds, and divisions of areas of power that are the causes of conflict and strained relations between communities in Abat. These factors have an impact on the arrangement of services in the Congregation and the social life of the people. Therefore, the church needs to renew its understanding of politics as a vessel for preaching and glorifying God, by presenting the values of God's kingdom which is full of peace, justice, and freedom of life.